KONTROL POLITIK BIROKRASI DALAM KEBIJAKAN PUBLIK - Mashur Hasan Bisri (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
Separation of powers provides norms and values that make a difference even the never-ending debate about divisions and work programs in the public policy process between politics and administrative that often occur in the system of relationships between the executive and legislative. This separation in politics and administration as a separation of related structural tasks with policy recommendations, regulation and control (control), ownership and distribution of resources, and so on. This happens that bureaucracy often plays for interference in the policy sphere so there is little intervention by bureaucrats to policy matters and is also done by politicians to in administration.Politik and administration as the distribution of values, costs, and profits, as a whole participates in this distribution process and in it the bureaucracy has the opportunity to submit proposals to policy makers, using discretion, the process in the implementation of policies, forming policies formulated by elected officials.DOI: https://doi.org/10.26905/pjiap.v2i2.1934